Modeling Air pollutin Due to Open Burning Of Scrap Tires In Rhinehart USA. - Gooi, Bee Sung; Koh, Hock Lye; Md Ismail, Ahmad Izani (2005)
With approximately one scrap tire being generated per person each year in the USA, scrap tires present a disposal problem. Uncontrolled open burning of tires prodeuces many toxic products of incomplete combustion into the atmosphere. Air emissions from open burning of tires have been shown to be more toxic than those from combustor regardless of the fuel.....